Aphrodisiac Effect of Cultured Cordyceps militaris in Aged Male Rats - Saksopha, Suphaphorn; Preedapirom, Watcharaporn; Singpoonga, Natthapong; Chaiprasart, Peerasak; Taepavarapruk, Pornnarin (Journal of Basic and Applied Pharmacology, 2019)
Cordyceps militaris has been well known as an elixir since ancient times. Due to its highly priced and its scarcity of this natural fungus, the cultured C. militaris (CCM) has been developed and increasingly consumed for health-promoting effects. In this study, C. militaris was cultured in the cereal grain culture medium. Since its effect has not yet been extensively studied, this study aimed to investigate the effects of CCM focusing on its aphrodisiac effect in aging rat model with erectile dysfunction (ED). The results showed that aged rats treated with CCM (0.1, 0.5, and 1.0 g/kg BW) and sildenafil citrate (5 mg/kg BW) by gavage demonstrated significant improvements in their mating behavior and intracavernosal pressure responses to cavernous nerve stimulation. Serum testosterone level of these rats also increased markedly and a significant increase was seen in rats treated with CCM 1.0 g/kg BW. The level of penile nitric oxide synthase activity of aged rats treated with CCM 1.0 g/kg BW showed significantly higher than that of the aged vehicle group. Malondialdehyde levels in testicular tissues of aged rats treated with CCM were significantly reduced. The results obtained from this study indicated that CCM are able to restore erection functions in aged rats. Therefore, CCM could be used as aphrodisiacs for enhancing sexual performance and for the treatment of ED, especially in aged men.